EFEKTIFITAS LATIHAN ABDOMINAL STRETCHING TERHADAP INTENSITAS NYERI HAID (DISMENOREA) PADA REMAJA PUTRI - Rosita; Nurul fitri Sugiarti Syam; Ayu Lestari; Jumrah (Poltekkes Kemenkes Medan, 2021)
Menstrual pain (dysmenorrhea) is one of the menstrual disorders that most women experience in adolescents. With one of the nonpharmacological practice stretching techniques can be done with the goal of knowing if there is an application effect on the intensity of menstrual pain (dysmenorrhea) in adolescents women. The type of research is an experimental design with the design approach used is the pre test- post test control group design, which is done in SMKN 01 makassar 2020 with 32 people research respondents, according to the two-split criteria for interagency and control groups as the pre-and post data processing technique on each group. Based on data normality tests, non-distribution of normal results, the tests used were wilcoxon tests. Furthermore, the pre-post normality test of unregulated data control interventions using the mann-whitney test.Research shows that test results on the pre post interventions using wilcoxon tests came p value (0,000 < 0.05). control groups using mann-whitney tests got p value (0,000<0.05). Thus it may be determined that there is an intermediate effect on the intensity of menstrual pain (dysmenorrhea).Based on the results of this study is expected for all elements that include educational agencies, subsequent researchers, teenagers and communities are able to provide information about abdominal tracks exercises as non-pharmacological therapy to reduce the intensity of hairsty pain (dysmenornea).